Examining the relationship between hip strength and time to stabilization in collegiate volleyball players - Skammer, S.; Nakajima, M.; Wu, W.; Becker, J. (Journal of Athletic Training, 2019)
"Context: Dynamic postural stability is important for performance and injury prevention in sports with a high frequency of repeated jump landings. One method for assessing dynamic postural stability is by calculating the time to stabilization (TTS), or how quickly an individual can stabilize following a jump landing. Numerous studies have reported increased TTS in individuals with unstable joints. However, relatively few studies have examined factors infl uencing TTS performance in healthy individuals. Weakness of the hip musculature is one factor which has been associated with numerous lower extremity injuries and could infl uence TTS performance. The purpose of this study was to evaluate the relationship between hip strength and TTS performance in healthy collegiate athletes. Methods: Sixteen male collegiate volleyball players (age: 20.6 ± 1.4 years; playing experience: 8.3 ± 3.2 years) participated in this study. Muscle strength for the hip abductors, adductors, internal and external rotators, fl exors, and extensors was measured using hand held dynamometry. Participants performed a standing long jump onto a force plate sampling at 1000 Hz, landing on one foot. Jump distance was set to 70 cm and jump height to 50% of maximal vertical jump height. TTS was calculated in the anterior-posterior (AP), medial-lateral (ML), and vertical directions using a sequential averaging method generated from a custom Matlab code. A resultant TTS was also calculated from AP, ML, and vertical values. TTS values were calculated for both the right and the left legs and multiple linear regression was used to evaluate relationships between hip strength values and TTS measures. Results: Mean TTS values were 3.21 (± 0.52), 3.87 (± 0.91), 3.06 (± 0.66), and 5.93 (± 1.06) seconds in the anterior-posterior, mediolateral, vertical, and resultant directions, respectively. Muscle strength did not predict TTS in the anterior- posterior (R2 = 0.126, P = 0.591), medio-lateral (R2 = 0.072, P = 0.841), or vertical (R2 = 0.295, P = 0.087) directions. In the vertical direction, the only signifi cant muscle group were the extensors, with a p-value of .04. Regression coeffi cients and confi dence intervals for each muscle are shown in Table 1. Muscle strength also did not predict resultant TTS (R2= 0.106, P=0.685). Conclusions: Hip muscle strength did not predict TTS in this cohort of healthy individuals. However, previous studies report that hip muscle strength does infl uence TTS in athletes with a lateral ankle sprain. Thus, the relationship between hip strength and TTS performance appears to change with occurrence of injury. Further research is required to clarify the mechanisms responsible for this changing relationship."